Analysis of corner radius in dry micro WEDM - Chowdhury, Ahmed Ghalib Khan; Ali, Mohammad Yeakub; Banu, Asfana (International Journal of Mechanical Engineering and Robotics Research., 2018)
Dry micro WEDM is a machining process where gas is used as the dielectric medium instead of liquid. This process favored for its environmental friendly nature and its ability in machining complex intricate shapes with great precision. Regardless of its high precision, the machining precision of cutting sharp corners cannot be satisfied. Therefore, the purpose of this paper is to analyze the process parameters; gap voltage, wire tension, and air dielectric pressure to find the optimal parameters to minimize the radius during the sharp corner cutting of stainless steel workpiece. Compressed air was used as the dielectric fluid, whereas the electrode was a 70 micrometer tungsten wire. The experiments were design using full factorial method while the data were analyzed using analysis of variance (ANOVA). Based on ANOVA, gap voltage and wire tension had a major influence on the corner radius. The optimum parameters for minimum corner radius were found to be 85 V gap voltage, 0.16 N wire tension, and 0 MPa dielectric pressure.